2018
DOI: 10.1021/acs.jctc.7b01109
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Prediction of Mutation Effect on Drug Binding in HIV-1 Protease Using Alchemical Calculations

Abstract: Despite a large number of antiretroviral drugs targeting HIV-1 protease for inhibition, mutations in this protein during the course of patient treatment can render them inefficient. This emerging resistance inspired numerous computational studies of the HIV-1 protease aimed at predicting the effect of mutations on drug binding in terms of free binding energy ΔG, as well as in mechanistic terms. In this study, we analyze ten different protease-inhibitor complexes carrying major resistance-associated mutations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 88 publications
(150 reference statements)
6
35
0
Order By: Relevance
“…For this purpose, we performed MD simulations for the protease mutants and wildtype in inhibitor-bound and unbound state, where in the bound state the simulations were performed in both alternative protonation states of the catalytic residues of the active site, D25 and D25 , to account for asymmetry of this complex. This allows us to identify which protonation state is more likely for both wildtype and mutant complexes, as well as to increase the accuracy of the ∆∆G estimation, as we reported previously [17]. The resulting ∆∆G calculations (Tables 2 and S2) overall indicated a good agreement in discriminating resistant and sensitising effects of mutations on the protein-ligand binding, including the opposite effects of N88S towards IDV and APV.…”
Section: Estimation Of Resistance Factors From the Change In The Inhisupporting
confidence: 52%
See 1 more Smart Citation
“…For this purpose, we performed MD simulations for the protease mutants and wildtype in inhibitor-bound and unbound state, where in the bound state the simulations were performed in both alternative protonation states of the catalytic residues of the active site, D25 and D25 , to account for asymmetry of this complex. This allows us to identify which protonation state is more likely for both wildtype and mutant complexes, as well as to increase the accuracy of the ∆∆G estimation, as we reported previously [17]. The resulting ∆∆G calculations (Tables 2 and S2) overall indicated a good agreement in discriminating resistant and sensitising effects of mutations on the protein-ligand binding, including the opposite effects of N88S towards IDV and APV.…”
Section: Estimation Of Resistance Factors From the Change In The Inhisupporting
confidence: 52%
“…Numerous studies have addressed the molecular effects of RAMs. Some studies analyse the effects of selected major RAMs on binding of different inhibitors [10,11,12,13,14,15,16,17] and others the effect of different RAMs on binding of the same inhibitor [18,19,20,21,22,23,24,25,26,27]. Most of the studies are however focused on a single mutation-inhibitor combination, particularly for major RAMs outside of the binding pocket, and thus offer only a limited perspective on molecular mechanisms of the protease resistance.…”
Section: Orrespondencementioning
confidence: 99%
“…In turn, application of FEP to a vast range of protein-ligand systems revealed that the method can indeed deliver accurate relative binding affinity predictions with an error of <1 kcal mol À1 with respect to experiment. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] However, the application of FEP using most MD soware remains challenging, preventing its widescale uptake.…”
Section: Introductionmentioning
confidence: 99%
“…57 Notwithstanding the lack of consensus in the scientic community on this matter, our non-equilibrium protocols 58,59 have already provided high-accuracy predictions in a number of applications involving amino acid and nucleotide mutations. 27,29,34,35,59,60 Here, we use pmx to calculate the difference in binding free energy for 482 ligand perturbations across 13 different ligandprotein activity datasets in two contemporary force elds. The calculated free energy differences were combined into a consensus estimate from the results of both force elds providing further increase in accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the initial success of these drugs in clinical treatments of HIV‐infected patients, unfortunately, PR has evolved into mutants to weaken the clinical efficiency of PIs, leading to multidrug resistance (MDR) toward the existing drugs . Except for the experimental studies, different simulation methods were also employed to partially probe drug resistance induced by the mutated PR . It is worth noting that Schiffer's group used crystallography and simulations to study bindings of inhibitors to PR, and their results clarified drug‐resistant mechanism of mutations in PR and binding modes of inhibitors to PR .…”
Section: Introductionmentioning
confidence: 99%